A non-contact ultrasonic auxiliary briquetting method for lithium battery ultrafine powder pulse plug flow conveying
Patent Information
- Application Number
- CN202611209805.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0005]本发明的目的在于克服现有技术中锂电超微粉体脉冲成栓成功率低、接触式成栓结构易引入异物污染的不足,提供一种锂电超微粉体脉冲栓流输送的非接触超声辅助成栓方法以满足锂电生产中的洁净输送要求
1、超声振动单元布设于管道外壁,无任何运动部件接触物料,从根源上避免了机械磨损产生的金属、非金属异物混入,完全符合锂电电极材料ppb级异物管控要求,无安全隐患;
Smart Images

Figure CN122704686B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder pneumatic conveying technology, and in particular to a pulse thrombus conveying method suitable for ultrafine powder content in new energy lithium batteries. Background Technology
[0002] In the production process of new energy lithium battery electrodes, the amount of ultrafine powders such as nano-conductive agents and nano-functional additives added is usually less than 1% of the total formula. These are materials with extremely small dosages, and their delivery and metering accuracy directly affects the consistency of the electrode slurry and the electrochemical performance of the battery. Pulsed micro-bolus flow conveying uses periodic pulsed airflow to cut the material column to form micro-boluses, and the delivery of small dosages is achieved by counting the number of micro-boluses. This is currently a relatively advanced high-precision delivery solution for ultrafine powders.
[0003] However, existing pulsed plug flow conveying technology has significant drawbacks when applied to lithium battery ultrafine powders: First, lithium battery ultrafine powders are mostly nanometer to submicron in size, with strong van der Waals forces, high cohesion, and poor permeability between particles. When using traditional pure airflow cutting methods, it is difficult to form dense and regular plugs, which easily leads to plug breakage and scattering. The plug formation success rate is generally less than 65%, and the plug quality deviation exceeds ±15%, which cannot meet the requirements of high-precision conveying. Second, in order to improve the plug formation effect, some solutions adopt mechanical stirring and extrusion plug formation structures. However, the moving parts are in direct contact with the powder, and the wear debris under long-term operation can introduce magnetic or non-metallic foreign objects, which does not meet the ppb-level foreign object control requirements of lithium battery electrode materials and poses a safety hazard of internal short circuit in the battery. Third, the contact vibration arch breaking structure also has the risk of component wear and contamination, and high-frequency vibration can easily aggravate the static electricity accumulation of powder, which is inconsistent with the explosion-proof safety requirements of lithium battery workshops.
[0004] Therefore, developing a contactless, low-pollution pulse thrombus formation method that can effectively improve the thrombus formation stability of ultrafine powders is a technical problem that urgently needs to be solved in the field of high-precision clean delivery of lithium battery ultrafine powders. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies, such as low success rate of pulsed thrombus formation of lithium battery ultrafine powder and easy introduction of foreign matter contamination by contact thrombus formation structure, and to provide a non-contact ultrasonic-assisted thrombus formation method for pulsed thrombus flow transportation of lithium battery ultrafine powder to meet the clean transportation requirements in lithium battery production.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: A non-contact ultrasonic-assisted thrombus formation method for pulsed thrombus delivery of lithium battery ultrafine powder includes the following steps: S1 Pre-fluidization treatment: The lithium battery ultrafine powder to be transported is sent into the pre-fluidization chamber upstream of the plugging section. Dry inert gas is introduced into the pre-fluidization chamber to put the ultrafine powder in a quasi-fluidized state, break up macroscopic agglomerates, and improve the powder flowability and air permeability. S2 Non-contact Ultrasonic Assisted Pretreatment: When the pre-fluidized powder enters the slug-forming section of the pipeline, the ultrasonic vibration unit installed on the outer wall of the slug-forming section of the pipeline is activated. The ultrasonic vibration unit is symmetrically arranged along the circumference of the slug-forming section of the pipeline. It transmits high-frequency micro-amplitude vibration to the powder inside the pipe through the pipe wall. Without contacting the powder, it breaks up the soft agglomerates of the powder and reduces the cohesive force between particles, so that the powder presents a uniform continuous column state. S3 Pulse Air Synchronous Cutting and Bolting: While the ultrasonic vibration is in effect, a pulse airflow is introduced into the bolting section to cut the continuous column of material that has been pretreated by ultrasonication and form regular micro bolts; The triggering of the pulse airflow is linked to the ultrasonic vibration unit: The ultrasonic vibration unit is turned on 30ms~100ms in advance before the pulse airflow is triggered, and is turned off 50ms~150ms after the pulse airflow ends. S4 Stable Bolt Conveying: The generated micro-bolts are conveyed forward along the main conveying pipe under the propulsion of the conveying airflow. The ultrasonic vibration unit continuously acts on the bolting section of the pipe to maintain the stability of the continuous bolting process, while reducing the adhesion and residue of powder on the pipe wall.
[0007] Furthermore, the number of ultrasonic vibration units is 2 to 4, and the axial coverage length matches the length of the plug section to ensure that the powder inside the tube is subjected to uniform force.
[0008] Furthermore, the dry inert gas is dry nitrogen or argon. The inert atmosphere throughout the process can prevent the oxidation of highly active powders and reduce the risk of electrostatic discharge.
[0009] Furthermore, the lithium battery ultrafine powder is any one of the following: nano-conductive carbon black for lithium battery electrodes, carbon nanotube powder, nano-silicon powder, and nano-oxide additives, with an average particle size of 10nm~500nm.
[0010] Furthermore, the inner diameter of the embossed section of the pipe is 8mm~20mm, and the roughness of the inner wall of the pipe is Ra≤0.2μm, which reduces pipe wall adhesion and flow resistance.
[0011] Compared with the prior art, the present invention has the following beneficial effects: 1. The ultrasonic vibration unit is installed on the outer wall of the pipe, with no moving parts in contact with the material. This fundamentally avoids the mixing of metal and non-metal foreign objects caused by mechanical wear, fully meeting the ppb-level foreign object control requirements for lithium battery electrode materials, and eliminating any safety hazards. 2. Through dual pretreatment of pre-fluidization and circumferential uniform ultrasonic vibration, the macroscopic and soft agglomerates of nanoparticles are effectively dispersed. Combined with time-linked pulse cutting, the success rate of plug formation is greatly improved and the quality deviation of the plugs is significantly reduced. 3. Circumferential symmetrical vibration eliminates radial density segregation of the material column, and time-sequential linkage control ensures the regularity of the head and tail structure of the material plug, significantly improving the uniformity of material plug density and greatly reducing the probability of plug breakage and scattering during the conveying process. 4. Ultrasonic vibration can reduce the adhesion of powder to the inner wall of the pipe through the transmission of the pipe wall, reduce the amount of material residue, and reduce the risk of cross-contamination during material change. 5. It adopts a pipe wall conduction vibration method, without internal component friction electrification, and with the inert gas transportation environment, it meets the explosion-proof safety requirements of lithium battery workshops. Attached Figure Description
[0012] Figure 1 This is a schematic diagram of the non-contact ultrasonic-assisted thrombus delivery device according to an embodiment of the present invention.
[0013] In the diagram: 1-Pre-fluidization chamber, 2-Microporous breathable plate, 3-Fluidizing gas inlet, 4-Buried section pipe, 5-Ultrasonic vibration unit, 6-Pulse air knife, 7-Main delivery pipe. In the diagram, the microporous breathable plate 2 is visible at the bottom of the pre-fluidization chamber 1. Detailed Implementation
[0014] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Example
[0015] This embodiment focuses on pulsed embolization using nano-conductive carbon black powder (average particle size 25nm, specific surface area 60m² / g) for lithium batteries, employing the method described in this invention, as follows: The first step is pre-fluidization treatment: Nano-conductive carbon black is fed into a pre-fluidization chamber 1 with an inner diameter of 15 mm. A microporous permeable plate 2 is installed at the bottom of the pre-fluidization chamber 1. Dry nitrogen gas with a dew point of -60℃ is introduced through the fluidizing gas inlet 3, and the gas velocity is controlled at 0.06 m / s to put the powder in a quasi-fluidized state, which facilitates the dispersal of large agglomerates. The pre-fluidization gas velocity setting is based on the theoretical calculation of the critical fluidization velocity of nano-powders in this field. For carbon-based / oxide ultrafine powders with a particle size of 10~500 nm, the critical fluidization velocity is about 0.015~0.08 m / s. Within this range, it can ensure that the powder enters the fluidized state and disperses large agglomerates, while preventing fine powder from being blown out due to excessive gas velocity, thus avoiding material loss and concentration fluctuations.
[0016] The pre-fluidization treatment in this invention can significantly reduce the fluctuation of powder bulk density, providing a stable material column base for subsequent uniform slugging.
[0017] After pre-fluidization, non-contact ultrasonic-assisted pretreatment is performed. The pre-fluidized powder enters the slug-forming section pipe 4 with an inner diameter of 10 mm and a length of 60 mm. The smoothness (roughness) Ra of the inner wall of the pipe is 0.18 μm. Two piezoelectric ultrasonic vibration units 5 are symmetrically arranged circumferentially on the outer wall of the pipe, with a vibration frequency of 28 kHz and a single peak amplitude of 12 μm. After the powder enters the slug-forming section, the ultrasonic vibration is transmitted to the powder through the pipe wall, breaking up soft agglomerates and reducing cohesion.
[0018] The symmetrical arrangement of ultrasonic vibration units on the outer wall of the puncture section of the pipe is based on the requirement of uniform stress on the powder. Unilateral ultrasonic vibration will lead to uneven distribution of vibration intensity of powder on the cross-section of the pipe. Agglomerates near the vibration source side are fully dispersed, while those far away are not sufficiently dispersed, which can easily cause different densities in the material column (density segregation). The symmetrical arrangement of 2 to 4 vibration sources on the circumference can greatly improve the uniformity of the vibration field inside the pipe, ensuring that the pretreatment effect of the entire cross-section of the material column is consistent. In addition, in this embodiment, the vibration frequency is set to 28kHz and the single peak amplitude is 12μm. This design is based on the matching relationship between the binding energy of nanoagglomerates and vibration energy. Those skilled in the art know that the soft agglomeration binding energy dominated by van der Waals forces between nanoparticles is about 10. -18 ~10 -16 J. The ultrasonic vibration of this frequency band and amplitude can transmit sufficient alternating stress to the powder through the pipe wall, overcome van der Waals forces and thus disperse soft agglomerates; at the same time, it avoids the frequency band of powder resonance and dust generation, avoids excessive fluidization that will damage the continuity of the material column, and will not cause significant electrostatic accumulation.
[0019] The above-mentioned vibration frequency and amplitude settings greatly improve the dispersibility of soft agglomerates and significantly reduce the dynamic cohesive force of powder, providing a homogeneous column for pulse cutting.
[0020] The main purpose of performing non-contact ultrasonic-assisted pretreatment after pre-fluidization is to eliminate the radial density difference of the material column, improve the uniformity of the density of the material plug cross section, and reduce the risk of plug breakage caused by material powder segregation.
[0021] After the initial pretreatment, pulsed air synchronous cutting and plug formation are performed: a pulsed air knife 6 is installed on the side of the plug formation section, using a linkage control method. The ultrasonic vibration unit 5 is activated 60ms in advance, followed by triggering a pulsed airflow with a pulse pressure of 0.2MPa, a pulse width of 120ms, and a pulse frequency of 4Hz. The pulsed airflow cuts the continuous column of material, forming micro-plugs. After the pulse ends, the ultrasonic vibration is deactivated after a 100ms delay. The advance activation time of the ultrasonic vibration unit is based on the powder stress response and relaxation time: the response time of nanoparticles from static to vibration-dispersed steady state is about 20~80ms. Activating it 60ms in advance ensures that the powder is in the optimal dispersion state during pulse cutting. The delayed deactivation time is based on the initial structural stabilization time of the plug. For example, the front structure of the plug is loose after cutting. Continuous vibration can help the plug to form a dense structure. Within the delay time range of 50~150ms, the initial shaping process of the plug can be covered, and the tail of the plug will not collapse due to excessive vibration.
[0022] The steps described above in this embodiment improve the uniformity and regularity of the bolt cross-section, reduce the amount of loose powder at the head and tail of the bolt, and further reduce the deviation between the quality of individual bolts.
[0023] Finally, the stable delivery of the plugs: the micro-plugs generated in the aforementioned steps are delivered forward along the main delivery pipe 7 under the impetus of nitrogen gas, with a delivery gas velocity of 5 m / s.
[0024] Testing showed that the success rate of plug formation in this embodiment was significantly improved compared to traditional plug formation methods, with an average plug mass of 12.4 mg and a much lower plug mass deviation than traditional methods. After 2 hours of continuous operation, the residual amount on the inner wall of the plug-formed section of the pipe was 0.028 mg, and no new metallic foreign matter was detected. The plug cross-section showed uniform density. This embodiment fully meets the high-precision and clean transportation requirements of new energy battery manufacturers for lithium battery ultrafine powder during the production process.
[0025] Comparative Example 1 Using the same powder, pipeline, and pulse parameters as in Example 1, only the ultrasonic vibration unit was turned off, with all other conditions remaining the same. The test results were as follows: the success rate of plug formation was less than 65%, the mass deviation of the plug exceeded ±15%, the residual amount on the inner wall of the pipeline was 0.11 mg, and there were obvious phenomena of plug breakage and loose plugs.
[0026] Comparative Example 2 Using the same parameters as in Example 1, except that the ultrasonic vibration unit was changed to a single-sided arrangement, without timing linkage control, the test results were as follows: the success rate of plug formation was between 70-75%, the plug quality deviation was about ±12%, and the plugs had problems such as uneven density on one side and excessive powder at the edges.
[0027] The comparison between the embodiments and comparative examples shows that the non-contact ultrasonic-assisted thrombus formation method with circumferential symmetrical arrangement and time-series linkage described in this invention can significantly improve the thrombus formation success rate and uniformity of ultrafine powders, and has no risk of contact contamination, thus meeting the clean transportation requirements of lithium battery ultrafine powders.
[0028] The results of Comparative Examples 1 and 2 are at most applicable to ordinary lithium battery manufacturers, but they do not meet the requirements for clean transportation of lithium battery ultrafine powders used in the production of lithium batteries for new energy vehicles, especially those used in major new energy vehicles.
[0029] Of course, other factors also affect the success rate of plug formation and the quality deviation of the plug in the embodiments of the present invention, such as changes in the vacuum degree and dryness in the chamber and pipeline, and the quality of the material and surface treatment (such as smoothness) of the material silo, especially the plug-forming section of the pipeline. Since the powder being transported is an ultrafine powder, the pipeline material (affecting ultrasonic vibration) and the smoothness of the inner wall surface will affect the effect. However, if the influence of the pipeline material and the smoothness of the inner wall is to be considered, the relationship between the material of the ultrafine powder being transported and the pipeline material must be considered. Therefore, the present invention only limits the surface roughness (smoothness) of the inner wall of the pipeline to Ra≤0.2μm. The pipeline material is not limited and commonly used pipeline materials in the art can be used, such as high-purity electropolished 316L stainless steel pipe (inner wall Ra≤0.2μm, passivated treatment). At the same time, the above-mentioned influencing factors can be adjusted by the performance of the equipment or as needed. These are conventional techniques mastered by those skilled in the art, so the present invention will not limit or describe them in detail.
[0030] The above description is merely a specific embodiment of the present invention and is not intended to limit the technical scope of the present invention. Any non-creative modifications and substitutions made by those skilled in the art based on the technical solutions of the present invention shall fall within the protection scope of the present invention.
Claims
1. A non-contact ultrasonic-assisted thrombus formation method for pulsed thrombus delivery of lithium battery ultrafine powder, characterized in that, Includes the following steps: S1 Pre-fluidization treatment: The lithium battery ultrafine powder to be transported is fed into the pre-fluidization chamber upstream of the plugging section. Dry inert gas is introduced into the pre-fluidization chamber to put the ultrafine powder into a quasi-fluidized state and break up the agglomerates. S2 Non-contact ultrasonic-assisted pretreatment: When the pre-fluidized powder enters the slug-forming section pipe, the ultrasonic vibration unit installed on the outer wall of the slug-forming section pipe is activated. The ultrasonic vibration unit is symmetrically arranged along the circumference of the slug-forming section pipe and transmits high-frequency micro-amplitude vibration to the powder inside the pipe through the pipe wall, thereby breaking up powder agglomerates and reducing interparticle cohesion without contacting the powder. S3 Pulsed Air Synchronous Cutting and Bolting: While the ultrasonic vibration is continuously applied, a pulsed airflow is introduced into the bolting section to cut the continuous column of material that has been pretreated by ultrasonication, forming regular micro-bolts; The triggering of the pulsed airflow is linked to the ultrasonic vibration unit: The ultrasonic vibration unit is turned on 30ms~100ms in advance before the pulsed airflow is triggered, and is turned off 50ms~150ms after the pulsed airflow ends. S4 Stable Bolt Conveying: The generated micro-bolts are conveyed forward along the main conveying pipe under the propulsion of the conveying airflow. The ultrasonic vibration unit continuously acts on the bolting section of the pipe to maintain the stability of the continuous bolting process.
2. The non-contact ultrasound-assisted thrombus formation method according to claim 1, characterized in that, The ultrasonic vibration unit has a vibration frequency of 20kHz to 40kHz and a single-peak amplitude of 5μm to 20μm.
3. The non-contact ultrasound-assisted thrombus formation method according to claim 1, characterized in that, The number of ultrasonic vibration units is 2 to 4, and the axial coverage length matches the length of the embolized section.
4. The non-contact ultrasound-assisted thrombus formation method according to claim 1, characterized in that, In step S1, the dry inert gas is dry nitrogen or argon, and the pre-fluidization gas velocity is controlled at 0.02m / s to 0.1m / s, so that the powder is fluidized and not blown out by the gas flow.
5. The non-contact ultrasound-assisted thrombus formation method according to claim 1, characterized in that, The lithium battery ultrafine powder is any one of the following: nano-conductive carbon black for lithium battery electrodes, carbon nanotube powder, nano-silicon powder, and nano-oxide additives, with an average particle size of 10nm~500nm.
6. The non-contact ultrasound-assisted thrombus formation method according to claim 1, characterized in that, The inner diameter of the puncture section of the pipe is 8mm~20mm, and the roughness of the inner wall of the pipe is Ra≤0.2μm.
Citation Information
Patent Citations
Ultrasonic fluidized atomic layer deposition device for fully dispersing and coating of micro-nanometer particles
CN109576673A
Ultrasonic precise feeding device and method for micron-sized powder particles
CN112478787A